2023
DOI: 10.1161/jaha.122.027480
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf Open Reading Frame (DWORF) Gene Therapy Ameliorated Duchenne Muscular Dystrophy Cardiomyopathy in Aged mdx Mice

Abstract: Background Cardiomyopathy is a leading health threat in Duchenne muscular dystrophy (DMD). Cytosolic calcium upregulation is implicated in DMD cardiomyopathy. Calcium is primarily removed from the cytosol by the sarcoendoplasmic reticulum calcium ATPase (SERCA). SERCA activity is reduced in DMD. Improving SERCA function may treat DMD cardiomyopathy. Dwarf open reading frame (DWORF) is a recently discovered positive regulator for SERCA, hence, a potential therapeutic target. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Hence, improving calcium S/ER reuptake appears to be ineffective in PLN-R14del cardiomyopathy. Therefore, in contrast to the protective effects of DWORF in other HF models, 14,17,39 its protective effect in PLN-R14del cardiomyopathy does not appear to be related to calcium handling. Based on the data presented above, we, therefore, consider it more likely that the protective effect of DWORF involves the prevention of abnormal S/ER cluster formation in PLN-R14del cardiomyopathy.…”
Section: Discussionmentioning
confidence: 74%
“…Hence, improving calcium S/ER reuptake appears to be ineffective in PLN-R14del cardiomyopathy. Therefore, in contrast to the protective effects of DWORF in other HF models, 14,17,39 its protective effect in PLN-R14del cardiomyopathy does not appear to be related to calcium handling. Based on the data presented above, we, therefore, consider it more likely that the protective effect of DWORF involves the prevention of abnormal S/ER cluster formation in PLN-R14del cardiomyopathy.…”
Section: Discussionmentioning
confidence: 74%
“…However, sarcolipin expression did not change with 4 days of low-intensity exercise involving 45 min of one-arm cranking followed by an 8 h walk in overweight individuals (Morales-Alamo et al, 2020). Moreover, Morales et al (2023) revealed that DWORF gene therapy improved treadmill performance in mice. However, it is not known whether different types of exercise or training interventions would induce DWORF expression and increase the amount of Ca 2+ pumped back into the sarcoplasmic reticulum in humans or rodent models.…”
Section: Role In Diseasementioning
confidence: 97%
“…Also playing a pivotal role in Ca 2+ homeostasis, SERCA contributes to muscle contraction by transporting cytosolic Ca 2+ back into the lumen of the sarcoplasmic reticulum (Xu & Van Remmen, 2021). In this context, the appropriate operation of SERCA appears essential for preservation of skeletal muscle health, consequently enhancing the overall well‐being of the individual (Morales et al., 2023). Therefore, enhancing SERCA activity through the upregulation of DWORF expression might offer a significant therapeutic strategy for increasing energy expenditure and facilitating enhanced energy use, ultimately leading to a decrease in fat accumulation.…”
Section: Introductionmentioning
confidence: 99%
“… 85 , 86 Given its potent stimulatory effects on SERCA2a and cardiomyocyte contractility, DWORF has recently emerged as a potential heart failure therapeutic. 84 , 87 , 88 Additionally, there has been a recent report of another SERCA-interacting protein, 48-AA pTUNAR, that enhances SERCA activity during neural differentiation. 58 Both DWORF and pTUNAR directly interact with SERCA, but their transmembrane domains lack the SERCA-inhibitory motif that is present in the SERCA-regulins, 12 , 58 thus indicating that their unique transmembrane domains may mediate their distinct ability to activate SERCA.…”
Section: The Functions Of Microproteins In Distinct Subcellular Domainsmentioning
confidence: 99%